Cross-sectional Comparison of the Epidemiology of DSM-5 Generalized Anxiety Disorder Across the Globe - Ruscio, Ayelet Meron; Hallion, Lauren S; Lim, Carmen C W; Aguilar-Gaxiola, Sergio; Al-Hamzawi, Ali; Alonso, Jordi; Andrade, Laura Helena; Borges, Guilherme; Bromet, Evelyn J; Bunting, Brendan; Caldas de Almeida, José Miguel; Demyttenaere, Koen; et al. (JAMA psychiatry (Chicago, Ill.), 2017)
Generalized anxiety disorder (GAD) is poorly understood compared with other anxiety disorders, and debates persist about the seriousness of this disorder. Few data exist on GAD outside a small number of affluent, industrialized nations. No population-based data exist on GAD as it is currently defined in DSM-5. To provide the first epidemiologic data on DSM-5 GAD and explore cross-national differences in its prevalence, course, correlates, and impact. Data come from the World Health Organization World Mental Health Survey Initiative. Cross-sectional general population surveys were carried out in 26 countries using a consistent research protocol and assessment instrument. A total of 147 261 adults from representative household samples were interviewed face-to-face in the community. The surveys were conducted between 2001 and 2012. Data analysis was performed from July 22, 2015, to December 12, 2016. The Composite International Diagnostic Interview was used to assess GAD along with comorbid disorders, role impairment, and help seeking. Respondents were 147 261 adults aged 18 to 99 years. The surveys had a weighted mean response rate of 69.5%. Across surveys, DSM-5 GAD had a combined lifetime prevalence (SE) of 3.7% (0.1%), 12-month prevalence of 1.8% (0.1%), and 30-day prevalence of 0.8% (0). Prevalence estimates varied widely across countries, with lifetime prevalence highest in high-income countries (5.0% [0.1%]), lower in middle-income countries (2.8% [0.1%]), and lowest in low-income countries (1.6% [0.1%]). Generalized anxiety disorder typically begins in adulthood and persists over time, although onset is later and clinical course is more persistent in lower-income countries. Lifetime comorbidity is high (81.9% [0.7%]), particularly with mood (63.0% [0.9%]) and other anxiety (51.7% [0.9%]) disorders. Severe role impairment is common across life domains (50.6% [1.2%]), particularly in high-income countries. Treatment is sought by approximately half of affected individuals (49.2% [1.2%]), especially those with severe role impairment (59.4% [1.8%]) or comorbid disorders (55.8% [1.4%]) and those living in high-income countries (59.0% [1.3%]). The findings of this study show that DSM-5 GAD is more prevalent than DSM-IV GAD and is associated with substantial role impairment. The disorder is especially common and impairing in high-income countries despite a negative association between GAD and socioeconomic status within countries. These results underscore the public health significance of GAD across the globe while uncovering cross-national differences in prevalence, course, and impairment that require further investigation.